2020
DOI: 10.1037/aca0000268
|View full text |Cite
|
Sign up to set email alerts
|

From dropping out to dropping in: Exploring why individuals cease participation in musical activities and the support needed to reengage them.

Abstract: From dropping out to dropping in: Exploring why individuals cease participation in musical activities and the support needed to re-engage them. Psychology of Aesthetics, Creativity, and the Arts, advance online publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Krause et al (2020, p. 412) found that people's "assumption of what a music participant is or should be included the perception that an individual must possess specific qualities and/or skills in order to take part". Assumptions included a certain level of musical ability, and as Krause et al (2020) argued, music educators and facilitators must challenge held assumptions and ideologies to remove such barriers to musical participation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Krause et al (2020, p. 412) found that people's "assumption of what a music participant is or should be included the perception that an individual must possess specific qualities and/or skills in order to take part". Assumptions included a certain level of musical ability, and as Krause et al (2020) argued, music educators and facilitators must challenge held assumptions and ideologies to remove such barriers to musical participation.…”
Section: Discussionmentioning
confidence: 99%
“…These beliefs may be informed, in part, by portrayals in popular culture of "good singing". In an examination of the reasons for dropping out of musical activities, Krause et al (2020) found that participants made assumptions regarding what participation means, including a belief that a person must possess a certain level of skill or musical ability to participate in musical activities. Therefore, it is important to understand general perceptions of "good singing", as this is the likely benchmark against which people will judge whether they are able to participate in singing activities.…”
Section: Abstract: Singing Perception Performance Quality Singing Sty...mentioning
confidence: 99%
“…The data used in this research were obtained as a part of a larger study considering musical participation (see also Krause, Kirby, Dieckmann, & Davidson, 2019;Krause, North, & Davidson, 2019). The present research employed the data concerning the named social-psychological variables, to quantitatively examine the differences between those who were currently participating in a musical activity and those who had ceased their participation.…”
Section: Participantsmentioning
confidence: 99%
“…A formal study of musical dropout was conducted by Krause, Kirby, Dieckmann, and Davidson (2019). They found four factors that tended to be responsible for dropout: "access and opportunity," "activity experience," "obligations," and "difficulty with practicing."…”
mentioning
confidence: 99%